Pengaruh Viral Marketing dan Live Stream Terhadap Purchase Intention - Indrawan, Luthfi Ananda; Pradana, Bayu Ilham (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2023)
The existence of a trend called Racun Tiktok has an adverse effect in causing the impulsive and consumptive nature of social media users. In addition, TikTok has made shoppable live streams a new (and main) trend in online shopping at the TikTok Shop, because through this feature sellers and buyers can interact in two directions. This study aims to examine the effect of Viral marketing and Live stream on Purchase intentions for Skintific Products on TikTok. This research is a quantitative study with independent variables, namely Viral marketing (X1), Live stream (X2) and the dependent variable, namely Purchase intention (Y). The population studied is TikTok users in Indonesia who know Live TikTok and content that is currently viral from Skintific with a sample size of 134 responses. This study used a non-probability sampling technique with a purposive sampling method. Multiple linear analysis is used as a data analysis technique in this study. Based on the results of data analysis, all hypotheses can be accepted and it can be concluded that: 1) There is an influence between Viral marketing on Purchase intention. 2) There is an influence between Live stream on Purchase intention.   Abstrak Adanya tren yang bernama Racun TikTok memberi dampak buruk dalam menimbulkan sifat impulsif dan konsumtif pengguna sosial media. Selain itu TikTok telah menjadikan shoppable live stream sebuah tren baru (dan utama) dalam belanja online di TikTok Shop, karena lewat fitur ini penjual dan pembeli bisa berinteraksi dua arah. Penelitian ini bertujuan untuk menguji pengaruh Viral marketing dan Live stream terhadap Purchase intention Pada Produk Skintific di TikTok. Penelitian ini merupakan penelitian kuantitatif dengan variabel independent yaitu Viral marketing (X1), Live stream (X2) dan variabel dependen yaitu Purchase intention (Y). Populasi yang diteliti merupakan pengguna TikTok di Indonesia yang mengetahui Live TikTok dan konten yang sedang viral dari Skintific dengan jumlah sampel sebesar 134 respon. Penelitian ini menggunakan teknik non-probability sampling dengan metode purposive sampling. Analisis linier berganda digunakan sebagai teknik analisis data pada penelitian ini. Berdasarkan hasil analisis data, semua hipotesis dapat diterima dan dapat disimpulkan bahwa: 1) Terdapat pengaruh antara Viral marketing terhadap Purchase intention. 2) Terdapat pengaruh antara Live stream terhadap Purchase intention.